Multilocus sequence typing (MLST) of clinical and environmental isolates of Cryptococcus neoformans and Cryptococcus gattii in six departments of Colombia reveals high genetic diversity - Norida Vélez; Patricia Escandón (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: The average annual incidence of cryptococcosis in Colombia is 0.23 cases per 100,000 inhabitants in the general population, and 1.1 cases per 1000 in inhabitants with Acquired Immune Deficiency Syndrome (AIDS). In addition, the causal fungus has been isolated from the environment, with serotypes A-B and C in different regions. This study aims to determine the genetic association between clinical and environmental isolates of C. neoformans/C. gattii in Colombia. METHODS: Multilocus sequence typing (MLST) was used to identify possible clones, providing information about the epidemiology, ecology, and etiology of this pathogen in Colombia. RESULTS: A total of 110 strains, both clinical (n=61) and environmental (n=49), with 21 MLST sequence types (ST) of C. neoformans (n=14STs) and C. gattii (n=7STs) were identified. The STs which shared clinical and environmental isolate sources were grouped in different geographical categories; for C. neoformans, ST93 was identified in six departments, ST77 in five departments; and for C. gattii, ST25 was identified in three departments and ST79 in two. CONCLUSIONS: High genetic diversity was found in isolates of C. neoformans/gattii by MLST, suggesting the presence of environmental sources harboring strains which may be sources of infection for humans, especially in immunocompromised patients; these data contribute to the information available in the country on the distribution and molecular variability of C. neoformans and C. gattii isolates recovered in Colombia.